Photocatalytic and surface consequences of thermal treatments on Pt nanoparticles onto carbon nitrides during CO2-to-CO conversion - S. Vaquero-Vílchez; P. Nimax; E. Valtierra-Martinez; I. Ayesta; I. Agirrezabal-Telleria (Journal of CO2 Utilization)
Photocatalysis is an emerging alternative to convert CO2 into relevant products, but it faces technological challenges related to charge recombination and low efficiency. Thermally coupled gas phase photocatalysis can address these issues by lowering reaction temperatures and improving process efficiency. This work demonstrates that defect engineering, combined with Pt impregnation at various metal dispersion and sizes, can enhance photocatalytic properties in g-C3N4 materials. Structural changes in g-C3N4 and Pt oxidation state modification, significantly impact CO productivity from CO2. This study investigates how thermal treatments in H2 affect defect and thus vacancy formation in g-C3N4. Materials with 2 wt% Pt2+ species generate C–N3 vacancies, while Pt0 species with the same content lead to both C–N3 and N–C3 vacancies– within g-C3N4. These differences exhibit distinct reaction trends under dark conditions or upon light irradiation. To further understand these effects, detailed XPS analyses clarify the impact of reaction conditions on the material after pretreatment and catalysis. The findings show that g-C3N4 materials can reform their C–Nbonds after electron excitation through light exposure, enhancing and stabilizing the reaction's productivity. As a result, CO productivities up to 1.1 mmol·gcat−1·h−1 are achieved. This work is expected to contribute to understanding the effect of thermal treatment on carbon nitrides, particularly regarding defect engineering, and more broadly, the effects of temperature in photocatalysis.